Pole vault academy
Pole Vault Academy is designed to provide athletes and coaches with a unique progression of technique, drills, and classroom instruction. The academy will prepare and equip you whether beginner or advanced, novice to world class athlete. You will leave with a new understanding of proper progressions of mechanics, training methods and winning techniques to take you to the next level.